Late-Stage Sulfoximidation of Electron-Rich Arenes by Photoredox Catalysis - Lämmermann, Henriette; Sudau, Alexander; Rackl, Daniel; Weinmann, Hilmar; Collins, Karl; Wortmann, Lars; Candish, Lisa; Hog, Daniel T.; Meier, Robin (Synlett, 2018)
The sulfoximine group has been reported as a versatile and beneficial functionality for pharmaceutical or agrochemical entities. Herein, we report the Csp2–H sulfoximidation of electron-rich arenes under the irradiation of blue light using an organic acridinium photocatalyst and molecular oxygen or peroxodisulfates as terminal oxidants. The method allows for the late-stage introduction of various sulfoximines onto complex bioactive compounds showing high functional group compatibility without the need for prefunctionalization.
Keywords: photocatalysis; C–H functionalization; sulfoximines; arylation; late-stage functionalization